Territorial Development of European Cross-Border Areas from the Perspective of Statistical Data and Analyses - Kaisto, Virpi (International Journal of Contemporary Economics and Administrative Sciences, 2016)
<span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri",sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: TR; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="TR">Border regions are often considered peripheral regions that lag behind in regional development. However, surprisingly few studies have applied statistical data and analyses to examine the territorial development of European border areas. This paper discusses the development of European cross-border areas (CBAs) from the perspective of statistical data and analyses. It considers the territorial development of the CBAs, and the specificities and challenges of statistical data and methods when studying such territorial development. The study makes use of data and methods developed in the Ulysses research project, which was carried out during 2010–2012 as part of the ESPON 2013 program. This paper illustrates how statistical analyses reveal the diverse development of European CBAs, and points out the kind of challenges faced in the statistical analyses of the territorial development of CBAs. The concepts of border area and ‘border effect’ are used to illustrate these. Lastly, the paper addresses the policy relevance of the research findings, and how this may affect the research process.